The Design & Implementation of CRM-Taxi Online in Indonesia - Rusdiaman Rauf; Hengki Wijaya; Ezra Tari (School of Business, IPB University (SB-IPB), 2022)
Lifestyle shifting is directly proportional to advances in information technology. These developments cannot be prevented or stopped, so everyone must keep up with the changes. System changes occur including in transportation. There are three big online taxis, namely: GoJek, Grab, and Uber, Maxim. TheirIts problems exist in regulation, drivers, consumers, and human resource development. Furthermore, the main tThings that need attention are the comfort and income of the community. This paper will describe how to solve problems between government, society, and online taxi entrepreneurs. The research approach used is development. Researchers are trying to find information to implement the program created. We have a solution framework that is thought of and constitutes an innovative idea based on two directions. CRM is proposed as a system used to help online taxi users avoid inconvenience problems. All parties must follow this change because society may not survive in the face of globalization if everyone does not want changes that are more effective and efficient changes. Changes were made to improve people's lives. Furthermore, as the main person in charge, the applicator must have a sophisticated system in developing human resources, especially the drivers they have. Keywords: online taxi, innovations, human resource, systems, aplicator